Green Zakat sebagai Instrumen Keuangan Sosial Islam dalam Mendukung Pencapaian Sustainable Development Goals (SDGs) - Istivaul Khasanah; Diah Putri Isnaini; Amalia Nuril Hidayati (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2026)
The achievement of the Sustainable Development Goals (SDGs) in Indonesia continues to face various challenges, particularly those related to poverty, social inequality, and increasing environmental degradation caused by climate change. These conditions highlight the need for an instrument capable of integrating social welfare objectives with environmental sustainability. This article aims to analyze the role of green zakat as an Islamic social finance instrument in supporting the achievement of the Sustainable Development Goals (SDGs). The study employs a descriptive qualitative approach using a library research method through the collection and analysis of various sources, including academic journals, books, official reports, and other relevant documents related to zakat, Islamic social finance, green economy, and sustainable development. The findings indicate that green zakat has significant potential to support the achievement of the SDGs through environmentally based economic empowerment programs, such as sustainable agriculture, reforestation, waste management, and the development of eco-friendly businesses for vulnerable communities. In addition to contributing to poverty alleviation, green zakat can support climate change mitigation efforts and environmental conservation in line with the principles of maqashid sharia. However, its implementation still faces several challenges, including limited public literacy, inadequate regulatory support, and suboptimal governance of environmental-based programs. Therefore, stronger collaboration among government institutions, zakat management organizations, and society is needed to develop a more effective green zakat model. Future studies are recommended to conduct empirical research to measure the impact of green zakat implementation on specific and measurable SDG indicators.